Exogenous Lipoid Pneumonia - Effendi, Tiar Oktavian; Setyawan, Ungky; Putra, Ngakan; Erawati, Dini (Universitaas Brawijaya, 2022)
Background : Lipoid pneumonia is a rare disease and usually reported as sporadic cases. Exogenous lipoid pneumonia is a more common form of lipoid pneumonia. Untypical characteristics makes incidence rate of this cases are often imprecise. The diagnosis is made from a history of lipid containing material aspiration, radiologic imaging, and histopathological examination. There is no treatment of choice because diagnosis of this cases are rarely made. Case Report : We report one case at Dr. Saiful Anwar hospital, a 35 years old man with accidental kerosene ingestion and aspiration. Based on examination of the patient, laboratory results, radiological imaging, and BAL fluid analysis and cytology, diagnosis of exogenous lipoid pneumonia was made. Our treatment of choice was combination of antibiotic, corticosteroid and BAL to manage this patient. After 2 weeks of treatment, there were improvements on clinical and radiological imaging. Conclusion: Exogenous lipoid pneumonia is a rare disease. Using antibiotic, corticosteroid, and BAL through bronchoscopy can be a therapeutic option that provides clinical and radiological improvement. Key words : Lipoid Pneumonia, Exogenous Lipoid Pneumonia, Treatment of Lipoid Pneumonia